Growth performance and apparent ileal digestibility of broiler chickens fed different levels of crude protein supplementation with lysine, methionine and threonine - Shazali, Nurhazirah; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Mohamad, Rosfarizan; Abdul Rahim, Raha (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
This experiment was conducted to determine the effects of reducing dietary crude protein with lysine, methionine and threonine supplementation on growth performance and apparent ileal digestibility of broiler chickens. A total of 288 male Cobb 500 chicks were allocated into 8 treatment groups and were fed with essential amino acids supplementation in low crude protein diet. Diets contain 21% crude protein until 18% crude protein and supplemented with lysine, methionine and threonine. This experiment was conducted for 6 weeks and the feed intake, body weight, feed conversion ratio were measured weekly. There was no significant different (P>0.05) in feed intake among the treatment groups. The reducing level of crude protein from 21% until 18% supplemented with amino acid was significantly (P<0.05) higher in body weight, average daily gain and total weight gain as compared with T1. Overall result shows dietary crude protein supplemented with amino acids improved growth performance and apparent nutrient digestibility of broiler chickens. However, reducing dietary CP up to 2% showed the best results, especially in weight gain, feed conversion ratio and nutrient digestibility. It is believed that by reducing the level of crude protein in the broiler diet and supplementing with amino acid may enhance the nutrients digestibility and contributes to a better performance.